2021
DOI: 10.3389/fonc.2021.679536
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Systemic Inflammation Markers in Predicting Clinical Stage T1 Renal Cell Carcinoma Pathologically Upstaged to T3a

Abstract: ObjectivesWe aimed to determine preoperative risk factors associated with pathologic T3a (pT3a) upstaging of clinical T1 (cT1) renal cell carcinomas (RCCs) and develop a novel model capable of accurately identifying those patients at high risk of harboring occult pT3a characteristics.MethodsA retrospective analysis of 1324 cT1 RCC patients who underwent partial nephrectomy (PN) or radical nephrectomy (RN) was performed. The study cohort was divided into training and testing datasets in a 70:30 ratio for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The C-index for the nomogram was 0.712 (95% CI, 0.638-0.785). Compared with other studies (20,21), the advantage of our study was that the ARFS nomogram was more objective and could be easily calculated with 4 preoperative quantitative risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…The C-index for the nomogram was 0.712 (95% CI, 0.638-0.785). Compared with other studies (20,21), the advantage of our study was that the ARFS nomogram was more objective and could be easily calculated with 4 preoperative quantitative risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…1 Clinically, T1 RCC tumors can be identified as more aggressive T3a masses after final pathology analysis post-PN, with prior publications reporting a 1.9%-14% incidence rate. [7][8][9] In large RCC tumors, extrarenal fat extension is usually grossly visible on computed tomography or magnetic resonance imaging, whereas microscopic examination is generally required for small tumors. 23 Thus, the vast majority of pathological T3a RCC tumors, upstaged from the clinical T1 stage, need a pathological diagnosis and cannot be detected by preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study indicated that RCC diameter, R.E.N.A.L. score, and systemic inflammatory response markers (such as lymphocyte to monocyte ratio) can be used to predict postoperative T3a upstaging 7 ; however, more accurate and better characterization of RCC is needed to predict preoperative T3a RCC upstaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of PN is to completely remove the tumor while preserving the surrounding structures, making less excision of the peritumoral tissue. However, it has led to increasing numbers of missing cases with adverse pathological features, such as sinus fat, calyx or venous infiltration ( 2 ).…”
Section: Introductionmentioning
confidence: 99%